Enhancing Pregnant Women's Capacity to Achieve Balanced Nutrition for Stunting Prevention - Yanti Puspita Sari; Hermalinda Herman; Meri Neherta; Vetty Priscilla; Wedya Wahyu; Dwi Novrianda; Ira Mulya Sari; Yelly Herien; Arif Rohman Mansur; Mutia Farlina; Deswita; Lili Fajria (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2026)
Stunting remains a serious public health issue in Indonesia, particularly among children under five years of age. One of the main causes of stunting is the lack of understanding and practice of balanced nutrition, especially among pregnant women and mothers with toddlers. This community service activity aims to improve the knowledge of pregnant women regarding balanced nutrition as an effort to prevent stunting. The implementation stages include preparation, execution, and monitoring and evaluation. The community service activity was carried out on August 27, 2025, in the working area of Bungus Health Center, Padang. The participants in the community service were 10 pregnant women. The activity lasted for 120 minutes, including a pre-test on pregnant women's knowledge of nutrition and pregnancy, blood sugar and hemoglobin tests to identify pregnancy complications, providing education on nutrition during pregnancy, and a post-test. The mean knowledge score increased from 7.10 before the intervention to 8.70 after the intervention. Statistical analysis using a paired t-test showed a significant improvement in knowledge (p = 0.005). These results indicate the need for periodic health education for pregnant women during antenatal visits, especially regarding pregnancy care related to meeting nutritional needs during pregnancy.